HATCHABILITY PERFORMANCE OF DIFFERENT COLOUR BROILER BREEDER STRAIN - Pandian, C; Omprakash, AV; Selvan, ST; Sudersan, A (Indian Journal of Veterinary Sciences and Biotechnology, 2014)
A study was conducted to compare the fertility and hatchability of Nandanam broiler I, Nandanam broiler II and Nandanam broiler III at the age of 28-58 weeks maintained at Poultry Research Station, Tamil Nadu Veterinary and Animal Sciences University, Chennai-51. The per cent fertility, hatchability on eggs set, on fertile eggs and embryonic mortality were worked out. The mean per cent fertility of different colour broiler breeder strain were differed significantly (P